EXPERIENCE GENERIC VALPROATE IN ADULTS WITH FOCAL EPILEPSY (RESULTS THE OBSERVATIONS IN MOSCOW HEALTH FACILITY OUTPATIENT NETWORK) - I. Yu. Artemova; O. L. Badalyan; M. A. Bogomazova; I. I. Zhuravleva; A. . Ismailov; E. G. Komelkova; L. N. Lesinker; Yu. I. Logvinov; O. V. Otcheskaya; S. V. Petrov; A. A. Savenkov; Yu. V. Solomatin; et al. (Эпилепсия и пароксизмальные состояния)
Abstract: In this article the results of the study of focal observations of interchangeability of generic Konvuleksa to retard and original probe Depakine chrono on Valparin XR (production Torrent Pharmaceuticals, India) in patients with various forms of epilepsy. In focal observations was attended by 30 patients with focal forms of epilepsy: 17 men and 13 women aged 23 to 62 years with different disease duration and the presence of seizures, which differ according to the type and etiology. Based on these results it can be concluded that the transfer of patients with previous therapy Valparin XR generally accompanied by a stable level of seizure control.